PERSEPSI PEREMPUAN GENERASI MILENIAL TERHADAP KEHADIRAN ANAK: KAJIAN PENDAHULUAN - Wardhana, Anastasya Eka; Yusuf, Husmiati (Politeknik Kesejahteraan Sosial Bandung, 2024)
The presence of children is interpreted as the hope of the family, the successor ofoffspring, and the bearer of happiness and blessings. But along with the times, manymarried couples choose not to have children, this is certainly contrary to theconstruction of Indonesian society related to the concept of the ideal family. This can beseen from the decline in Total Fertility Rate in Indonesia. This study used descriptivequantitative methods with purposive sampling techniques based on criteria, namelywomen aged 27-35 years who belonged to the millennial generation, a total of 50respondents. Primary data sources through online penelitians. This study uses Schmitt& Schmitt's theory of direct and constructive perception to see the influence of internaland external factors in the formation of perception. The results show that individualinternal and external factors influence millennial women's perceptions of the presenceof children in marriage. Then, the millennial generation, which prioritizes maturity,stability and readiness from various factors, interprets the presence of children in thefamily as not a necessity and does not make children the only source of happiness eventhough it is undeniable that children become a complement to the family. Furtherstudies are needed to obtain more comprehensive data. In addition, premaritaleducation and counseling programs, gender equality campaigns, community supportand social networks can be used as recommendations.Keywords:perception, millennial, child, marriage